Food Security of Kazakhstan in the Context of Global Challenges of the Green Economy, Renewable Energy: ARDL and NARDL Assessment - Kaliyeva, Assem; Abilda, Symbat (International Journal of Energy Economics and Policy, 2025)
In the face of global challenges such as depletion of natural resources, rapid urbanization, and soil degradation, the issue of ensuring food security for the state’s population is more urgent than ever. The purpose of this research is to assess the level of food security in Kazakhstan in the context of global issues such as green economy, renewable energy, and environmental security. For this purpose, the authors used linear and nonlinear autoregressive distributed lag (ARDL and NARDL) econometric estimation models. The following indicators were taken as available indicators for the period 1996-2021: Bonilla index (calculated by authors), Rural population (% of total population), Agricultural land (% of total land), Annual freshwater withdrawals, agriculture (% of total freshwater withdrawal), Renewable electricity output (% of total electricity output), Total natural resources rents (% of GDP), Carbon dioxide (CO2) emissions from Agriculture (Mt CO2e). As a result of the two models: In the long run, it was determined that Rural population, renewable electricity output have a positive impact on food availability, and Annual freshwater withdrawals, Total natural resources rents and Carbon dioxide (CO2) emissions from Agriculture have a negative impact on food import dependence. In the short run, it was determined that changes in Rural population, lag variable and changes and changes in lag variable of Annual freshwater withdrawals have a negative impact, and lag variable of renewable electricity output and change in lag variable of renewable electricity output have a positive impact. The results of the study indicate that the principles of green economy can be applied to ensure food security It shows the need to adhere to the most environmentally friendly methods and use renewable energy sources.